2022
DOI: 10.1101/2022.08.06.22278488
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk and Outcome of Second primary malignancy in patients with classical Hodgkin lymphoma

Abstract: BACKGROUND Hodgkin lymphoma survivors demonstrated increased risk of secondary primary malignancies (SPMs), but comprehensive analysis of the risk and outcome of SPMs in classical Hodgkin lymphoma (cHL) patients has not yet been reported. METHODS Patients with classical Hodgkin Lymphoma from 1975 to 2017 were identified from the Surveillance, Epidemiology and End Results (SEER) database. Standardized incidence ratios (SIRs) were calculated for the risk of solid and hematologic SPMs in cHL patients compared to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…[14,15] Whereas in 2020 a case-control study in China showed that first-line treatment and the effect of thoracic or mediastinal radiotherapy were independent factors that led to the death of patients with lymphoma from a second primary tumor. [16] In our study, it was found that treatment factors did not play an absolute role in the risk of developing SPMs, chemoradiotherapy did not directly affect the cumulative incidence of lymphoma producing different types of SPMs, but radiotherapy/ chemotherapy was a relevant factor for lymphoma producing specific types of SPMs. In specific subtypes of SPMs, the effect of radiotherapy or chemotherapy on the generation of SPMs is both protective and dangerous in patients with different clinical features.…”
Section: Discussionmentioning
confidence: 51%
“…[14,15] Whereas in 2020 a case-control study in China showed that first-line treatment and the effect of thoracic or mediastinal radiotherapy were independent factors that led to the death of patients with lymphoma from a second primary tumor. [16] In our study, it was found that treatment factors did not play an absolute role in the risk of developing SPMs, chemoradiotherapy did not directly affect the cumulative incidence of lymphoma producing different types of SPMs, but radiotherapy/ chemotherapy was a relevant factor for lymphoma producing specific types of SPMs. In specific subtypes of SPMs, the effect of radiotherapy or chemotherapy on the generation of SPMs is both protective and dangerous in patients with different clinical features.…”
Section: Discussionmentioning
confidence: 51%